Bone mineral density and protein derived food clusters from the Framingham Offspring Study - Mangano, Kelsey M. (J Acad Nutr Diet, 2015)
BACKGROUND: Dietary protein is beneficial to bone health; however, dietary patterns of protein intake and their relation with bone mineral density (BMD) have not been evaluated. OBJECTIVE: To examine the relation of dietary protein food clusters with BMD at the femoral neck, trochanter, total femur and lumbar spine among middle-aged and older men and women. DESIGN: Cross-sectional study. PARTICIPANTS AND SETTING: 2,758 community-dwelling individuals from the Framingham Offspring Study. METHODS: BMD was measured by Lunar DPX-L in 1996–2001. Dietary intakes were estimated using the Willett food frequency questionnaire in either 1995–1998 or 1998–2001, and the exam closest to a participant’s BMD measurement was used. Cluster analysis (fastclus procedure, k-means method) was used to classify participants into groups, determined by major sources of protein. Generalized linear regression was used to compare adjusted least-squares mean BMD across protein food clusters for all pairwise comparisons. RESULTS: From 2,758 participants (44% men; mean age 61 ± 9y, range 29–86y), five protein food clusters were identified (chicken, fish, processed foods, red meat, low-fat milk). Three of these food clusters showed associations with BMD. The red meat protein food cluster presented with significantly lower femoral neck BMD compared to the low-fat milk cluster (red meat: 0.898 ± 0.005 versus low-fat milk: 0.919 ± 0.007, p=0.04). Further, the processed foods protein cluster presented with significantly lower femoral neck BMD compared to the low fat milk cluster (processed foods: 0.897 ± 0.004 versus low-fat milk: 0.919 ± 0.007, p=0.02). A similar, yet non-significant trend was observed for other BMD sites examined. CONCLUSIONS: Diets with the greatest proportion of protein intake from red meat and processed foods may not be as beneficial to the skeleton compared to dietary patterns where the highest proportion of protein is derived from low-fat milk.